2006
DOI: 10.1021/ic061272r
|View full text |Cite
|
Sign up to set email alerts
|

Eu(III) and Tb(III) Luminescence Sensitized by Thiophenyl-Derivatized Nitrobenzoato Antennas

Abstract: Thiophenyl-derivatized nitrobenzoic acid ligands have been evaluated as possible sensitizers of Eu(III) and Tb(III) luminescence. The resulting solution and solid-state species were isolated and characterized by luminescence spectroscopy and X-ray crystallography. The Eu(III) complex with 2-nitro-3-thiophen-3-yl-benzoic acid, 1, crystallizes in the monoclinic space group C2/c with a = 28.569(3) A, b = 17.7726(18) A, c = 17.7073(18) A, beta= 126.849(2) degrees, and V = 7194.6(13) A3. The Tb(III) complex with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
70
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(79 citation statements)
references
References 49 publications
9
70
0
Order By: Relevance
“…The FT-IR spectrum of the HTPAC ligand evidences two intense bands at approximately 1450 and 1704 cm -1 , which are attributable to the symmetric υ s (C=O) and anti-symmetric υ as (C=O) vibration modes, respectively. In the cases of the IR spectra of 1-4, both of these C=O vibrational modes are shifted to lower wave numbers and split into two peaks ( [15,20,21] The IR spectra of 1 and 2 also exhibit a broad band at approximately 3451 and 3412 cm -1 , which is characteristic of an O-H stretching vibration υ(O-H), and thus suggestive of the presence of a coordinated water molecule in both complexes. Moreover, the red shifts observed for the C=N stretching frequencies of the nitrogen donors in the complexes 3 and 4 (1591 cm -1 in 3 and 1590 cm -1 in 4) in comparison with those of the free ligands phen (1613 cm -1 ) and bath (1608 cm -1 ) imply coordination of these ligands to the Tb 3+ cation in each case.…”
Section: Characterization Of Lanthanide Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…The FT-IR spectrum of the HTPAC ligand evidences two intense bands at approximately 1450 and 1704 cm -1 , which are attributable to the symmetric υ s (C=O) and anti-symmetric υ as (C=O) vibration modes, respectively. In the cases of the IR spectra of 1-4, both of these C=O vibrational modes are shifted to lower wave numbers and split into two peaks ( [15,20,21] The IR spectra of 1 and 2 also exhibit a broad band at approximately 3451 and 3412 cm -1 , which is characteristic of an O-H stretching vibration υ(O-H), and thus suggestive of the presence of a coordinated water molecule in both complexes. Moreover, the red shifts observed for the C=N stretching frequencies of the nitrogen donors in the complexes 3 and 4 (1591 cm -1 in 3 and 1590 cm -1 in 4) in comparison with those of the free ligands phen (1613 cm -1 ) and bath (1608 cm -1 ) imply coordination of these ligands to the Tb 3+ cation in each case.…”
Section: Characterization Of Lanthanide Complexesmentioning
confidence: 99%
“…[21,22] A preliminary study by Malta and coworkers [23] demonstrated that thiopheneacetic acid (HTPAC) can be used as a potential sensitizer for lanthanide emissions. However, to the best of our knowledge, systematic investigations of the luminescent properties of terbium thiopheneacetate complexes in the presence of bidentate nitrogen donors and the structural characterization of such complexes by single-crystal X-ray diffraction have not been reported previously.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the introduction of a nitro group in the 3 position dramatically diminishes the photoluminescence efficiency of the Tb 3+ -3-nitro-4-benzyloxy benzoate complex due to the existence of a pathway that permits dissipation of the excitation energy via the π*-n transition of the nitro group in conjunction with the ILCT band. 5 Studies by de Bettencourt-Dias et al 6 suggest that derivatization of benzoic acid analogues with thiophene has a beneficial tuning effect on the triplet state of the antenna which results in a higher emission quantum yield. This is a consequence of improved matching of the ligand and lanthanide ion excited states.…”
Section: Introductionmentioning
confidence: 99%
“…This type of compound has found a variety of applications in catalysis, [1][2][3][4][5][6] ceramics and electronic materials. [7,8] Lanthanide derivatives are frequently screened to form precursors for MOCVD and for emitting layers in polymer-based light-emitting diodes [9,10] Recently, europium(3+) and terbium(3+) compounds containing thiophenyl-derivatized nitrobenzoic acid [9] and 2-nitro-4-(thiophen-3-yl)benzoic acid [11] ligands were reported. In general, thiophene derivatives are attractive as organic ligands because of the simple formation of polymer films by voltammetric methods.…”
Section: Introductionmentioning
confidence: 99%